2013
DOI: 10.1007/s10067-012-2146-6
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model for remission and low disease activity in patients with established rheumatoid arthritis receiving TNF blockers

Abstract: The objective of this study was to identify predictors for remission or low disease activity (LDA) in established rheumatoid arthritis (RA) at 12 months of anti-TNF-α therapy. We have performed a prospective observational study in 90 consecutive patients with active RA receiving TNF-α inhibitors. Baseline and standard assessments were done every 3 months, including individual parameters (clinical and biological) and composite activity scores (28-joint disease activity score, DAS28). The primary outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…There are numerous therapeutic options for treating a candidate rheumatoid arthritis patient with bDMARDs, and therefore predictors of response are required to select the treatment to which the patient will best respond. The clinical predictors of response for TNFi are male sex, age ≤ 54 years old at the start of TNFi therapy, high baseline DAS28, concomitant treatment with cDMARDs, and negative or low levels of CRP . Regarding other biochemical predictors, 2 meta‐analyses (5561 and 5703 rheumatoid arthritis patients) did not find any association between the values of RF and anti‐CCP and response to TNFi therapy …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There are numerous therapeutic options for treating a candidate rheumatoid arthritis patient with bDMARDs, and therefore predictors of response are required to select the treatment to which the patient will best respond. The clinical predictors of response for TNFi are male sex, age ≤ 54 years old at the start of TNFi therapy, high baseline DAS28, concomitant treatment with cDMARDs, and negative or low levels of CRP . Regarding other biochemical predictors, 2 meta‐analyses (5561 and 5703 rheumatoid arthritis patients) did not find any association between the values of RF and anti‐CCP and response to TNFi therapy …”
Section: Discussionmentioning
confidence: 97%
“…The clinical predictors of response for TNFi are male sex, age ࣘ 54 years old at the start of TNFi therapy, high baseline DAS28, concomitant treatment with cDMARDs, and negative or low levels of CRP. [13][14][15]44 Regarding other biochemical predictors, 2 meta-analyses (5561 and 5703 rheumatoid arthritis patients) did not find any association between the values of RF and anti-CCP and response to TNFi therapy. 20,21 In our study, the multivariate analysis demonstrated that patients treated with tocilizumab reported higher response when they were bDMARD naive, when tocilizumab was administered subcutaneously, when a smaller number of previous biological therapies had been administered, when they were younger at diagnosis and beginning of treatment, and when baseline values of DAS28, NTJ, and NSJ were higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher anti-CCP and RF concentrations resulted associated with greater disease activity over time along with lower chance to achieve sustained remission in men with established RA mainly under csDMARDs background [32,33]. Similarly, baseline low RF and anti-CCP levels (arbitrarily chosen by the authors) were independently predictive of clinical remission and low disease activity achievement at 12 months in 90 Romanian RA patients starting their first TNFi.…”
Section: Disease Activitymentioning
confidence: 93%
“…It is well established that cigarette smoking reduces the clinical response to both methotrexate and tumour necrosis factor (TNF) inhibitors [ 89 , 90 ]. Cigarette smoking is strongly associated with the titres of RF [ 91 ], and it is noteworthy that a RF titre < 20 IU/ml was highly predictive for remission or low disease activity in RA patients with established disease receiving TNF inhibitors [ 92 ]. In this study RA patients with a RF titre < 20 IU/ml were significantly more likely (OR 18.9, 95% CI 10.79-38.36) to be in remission at 12 months than RA patients with a RF titre >20 IU/ml.…”
Section: Implications For Treatmentmentioning
confidence: 99%